CODE-MIXING BY CAPTAIN VINCENT RADITYA ON YOUTUBE - Anis Masruroh; Lilis Suryani (IKIP Siliwangi, 2024)
This research discusses about the use of code-mixing by the pilot and YouTuber Captain Vincent Raditya on his YouTube channel. Captain Vincent Raditya is often seen mixing Indonesian code into English or otherwise. Therefore, The aims of the research are to find out how many code mixing that is used and to know the most dominant code mixing. Code mixing can occur if a speaker uses a language predominantly and then inserts it with another language. This can occur related to character, social background, education level, religion, and limitations in language equivalent expressions. In this research, the writers used type code-mixing from Hoffman. There are 3 types of Code Mixing; intra-sentential mixing, intra-lexical code mixing, and involving a change a pronunciation. In this research the writers used qualitative method, the data were taken from video Captain Vincent Raditya on Youtube and analyzed by code-mixing, the data analysis of code-mixing is displayed as a precentage. The data shows that there are 3 kinds of code mixing that were used by Captain Vincent Raditya. First, type intra-sentential mixing with percentage (86%), intra-lexical code mixing (10%), and involving a change a pronunciation (4%). Based on the data, the most dominant types of code-mixing is used by Captain Vincent Raditya is types intra-sentential mixing with percentage 64 (64%) by inserts words, phrases, clauses, or sentences in his utterance.